HUBUNGAN TINGKAT KREATIVITAS DENGAN PRESTASI BELAJAR PADA SISWA SD KELAS V MIN 10 MUARA ENIM TAHUN 2020 - Berta Afriani; Hatta Salimi (Jurnal Kesehatan Abdurrahman, 2021)
Background: In the 1993 GBHN it is stated that the development of creativity (creativity) should start at an early age, namely in the family environment as the place of first education and in pre-school education. The purpose of this study is not yet known the correlation between the level of creativity and learning achievement in SD students of class V MIN 10 Muara Enim. Methods: This study used an analytic survey method with a cross sectional approach. The population of this study were all fifth grade students of SD MIN 10 Muara Enim, the sample in this study amounted to 40 respondents. Data analysis used univariate analysis and bivariate analysis using distribution tables and Chi-Square statistical tests, with a degree of confidence of 95%. Results: From the chi-square test, it was found that p value = 0.000 (p value> 0.05). Conclusion: There is a relationship between the level of creativity and learning achievement in SD students of class V MIN 10 Muara Enim.